تقويم كفايات تخطيط الدروس - جاكاريجا, كيتا; زيد اسماعيل, محمد; عبد العزيز بيومي, نشأت (جامعة الوادي University of Eloued, 2018)
سعت هذه الدّراسة إلى الكشف عن درجة كفايات تخطيط الدّروس لدى معلّمي اللّغة العربيّة في المرحلة الثّانويّة بالمدارس العربيّة في مالي، والتّعرّف عمّا إذا كانت توجد فروق ذات دلالة إحصائيّة عند مستوى (0,05) في درجات تخطيط الدّروس لديهم تعزى لمتغيّر نوع المؤهّل العلميّ. واستخدم الباحثون المنهج المسحيّ الوصفيّ معتمدِينَ على أداة استفتاء، وتكوّن مجتمع الدّراسة من جميع معلّمي اللّغة العربيّة في المرحلة الثّانويّة بالمدارس العربيّة في مالي، البالغ عددهم (143) معلّمًا. وأظهرت النّتائج أنّ درجة كفايات تخطيط الدّروس لدى أفراد مجتمع الدّراسة في مجال المقـدّمة التّمهيديّة، والمحـتوى، والأهداف السّلوكيّة، والأنشطة، على التّرتيب كبيرة، إذ تراوحت متوسطاتها الحسابيّة بين (4,07-3,57)، في حين توصلت الدّراسة إلى أنّ درجة كفايات تخطيط الدّروس لديهم في مجال إستراتيجيات التّدريس والوسائل التّعليميّة، وإستراتيجيات التّقويم متوسطة، حيث تراوحت متوسطاتها بين (2,78-2,77)، وكشفت الدّراسة عن وجود فروق ذات دلالة إحصائيّة بين درجات كفايات تخطيط الدّروس لدى أفراد مجتمع الدّراسة تعزى لمتغيّر نوع المؤهّل في جميع مجالات الدّراسة ما عدا مجال إستراتيجيات التّقويم لصالح التّربويّين. وخلصت الدّراسة إلى عددٍ من التّوصيات والمقترحات. This study sought to reveal the degree of competency lesson planning among Arabic language teachers in Arabic Secondary Schools in Mali, And to determine whether there were statistically significant differences at the level of )α≤0,05( in the grades of their lesson planning due to the variable type of academic qualification. The researchers employed descriptive survey approach to achieve the stated objectives Questionnaire was administered to (143) Arabic language teachers in Mali Arabic secondary schools. The results showed that the degree of lesson planning among the study community in the introductory field, educational content, Behavioral Objectives, and educational activities, respectively, Great degree, Their arithmetic averages ranged between (4,07-3,57). While the study found that the degree of planning their lessons in the areas of teaching strategies and teaching methods, and assessment strategies are medium, ranging in the arithmetic mean between (2,78-2,77), The study revealed the existence of statistically significant differences between the grades of their lesson planning due to the variable of the type of academic qualification in all fields of study to the field of evaluation strategies for the benefit of educators. the study concluded with a number of recommendations and proposals.
لدى معلمي اللغة العربية في المرحلة الثانوية
مقال
Keywords: الكفايات التّعليميّة؛ تخطيط الدّروس؛ المعلّمون؛ المرحلة الثّانويّة؛ المدارس العربيّة; lesson planning competency Evaluation; Arabic language teachers; secondary school Arabic schools